A comparative study on the adsorption of toxic cationic dyes by Judas tree (Cercis siliquastrum) seeds - Isik, Birol; Ugraskan, Volkan; Cakar, Fatih; Yazici, Ozlem (SPRINGER HEIDELBERG, 2024)
Cercis siliquastrum seeds were used for the adsorption of the basic dyes namely basic blue 9 and basic green 4 from the wastewater. Adsorption experiments were conducted under various conditions including different temperatures (25, 35, and 45 degrees C), pH (2-12), contact time (0-180 min), adsorbent amount (0.2-4.0 g/L), and concentration (10-50 mg/L). The adsorption processes were applied to various isotherms such as Freundlich, Langmuir, Dubinin-Radushkevich, and Harkins-Jura. Furthermore, different adsorption kinetic models including pseudo-first-order, pseudo-second-order, Boyd, and intraparticle diffusion were studied to comprehend the mechanism of the adsorption of the dyes. The results illustrated that the adsorption was best described by the Langmuir (r(2) = 0.9949 for basic blue 9 dye and r(2) = 0.9939 for basic green 4 dye at 25 degrees C). From the Langmuir isotherm, the q(m) value of basic blue 9 was found as 500.0 mg/g whereas those of basic green 4 was found as 243.9 mg/g at 25 degrees C. According to the thermodynamic parameters, it was determined that the adsorption process occurred endothermically and spontaneously for basic blue 9 and basic green 4 dyes. Considering the capacity of adsorption for both dyes, this study suggests that Cercis siliquastrum seeds are low-cost and environmentally friendly materials for the effective adsorption of basic dyes.
Keywords: Adsorption; Basic blue 9; Basic green 4; Cercis siliquastrum seeds; MALACHITE GREEN; ACTIVATED CARBON; AQUEOUS-SOLUTION; REMOVAL; EQUILIBRIUM; ISOTHERMS; ADSORBENT; POLYDOPAMINE; PERFORMANCE; Energy & Fuels; Engineering